Replication efficiency of bovine papillomavirus type 1 DNA depends on cis-acting sequences distinct from the replication origin. - Pierrefite, V (1995)
The viral elements required for the initiation of replication of bovine papillomavirus type 1 DNA include the origin region and two trans-acting factors, the E1 and E2 proteins. We now report that the replication efficiency of a DNA molecule which contains these three elements is modulated by other viral sequences. By measuring the extent of replication of deleted viral genomes in transfected mouse cells, we identified sequences required for maximal efficiency. Addition of these sequences to a construct carrying only the minimal origin region increased its replication. Among these cis-active elements, we identified a 69-bp fragment (nucleotides 4921 to 4990) which contains at least two binding sites for cellular proteins. One of them is the murine protein termed CDEBP, which recognizes the octameric motif ATCACGTG, identical to the yeast CDEI element. Either deletions affecting this CDEI box or a point mutation which impairs binding of CDEBP markedly decreased the extent of viral DNA replication. They had no detectable effect on viral transcription.